Integrative taxonomy approach to detect spatial and temporal variability of the Mediterranean benthic communities through artificial substrate units (ASUs) - Mugnai, Francesco; Mikac, Barbara; Colangelo, Marina Antonia; Matterson, Kenan Oguz; Abbiati, Marco; Costantini, Federica (Frontiers in Marine Science, 2023)
Monitoring spatial and temporal changes of marine benthic communities using standardized procedures is essential to take necessary steps towards conservation of marine ecosystems. In this study we combined Artificial Substrate Units (ASUs) for sampling of benthic communities, with integrative taxonomy approach that incorporated morphological identification of organisms and COI DNA metabarcoding, to characterize the diversity of communities at three locations across the Central Mediterranean Sea (Livorno and Palinuro, Italy; Rovinj, Croatia) in 2019 and 2020. Significant differences in the communities’ structure were observed both at large spatial scale between sampled locations, and at small spatial scale (less than ten kilometers) between sites. Moreover, significant temporal variability in species richness and structure of benthic assemblages was detected, with higher richness in 2020. Revealed variability can probably be attributed to the peculiar geomorphological, oceanographical, and ecological features of locations, but also to the influence of interplaying local chemical and physical factors and biological processes such as species settlement, competition, and migration that can act at small spatial and temporal scales. The similarity in the species composition and community structure accessed by morphological and metabarcoding approaches was low, with only 16% of the species (out of 133 species identified overall) commonly detected by both approaches. This is mostly both due to a lack of data on COI sequences of numerous benthic invertebrates in the public barcoding databases on the one hand, and difficulties in detecting small and cryptic taxa through morphological analyses on the other. This suggests that combining of two approaches is required to fully describe the biodiversity of benthic assemblages. Finally, comparison of the spatial variability of the benthic communities’ structure with two approaches at different taxonomic levels, indicated that genus and family levels give results that are consistent to those obtained by the species level. This suggests that family level might be satisfactory in monitoring the spatial-temporal variability of Mediterranean hard bottom benthic communities.